Mass spectrometry of macromolecular assemblies: preservation and dissociation - Benesch, J; Robinson, C (Elsevier, 2006)
Mass spectrometry not only plays a crucial role in the identification of proteins involved in the intricate interaction networks of the cell, but also is increasingly involved in the characterization of the non-covalent complexes formed by interacting partners. Recent developments have enabled the use of gas phase dissociation to probe oligomeric organization and topology, and increased understanding of the electrospray process is leading to knowledge of the structure of protein assemblies both in solution and in the gas phase.